Improving Employee Performance: Analysis of the Influence of Organizational Culture, Organizational Citizenship Behavior (OCB), and Work Ethic - Tiara Maharani; Mega Ayu Noviyanti; Siti Maryam (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In the face of increasingly fierce global competition, organizations are required to implement systems that involve Organizational Culture, Organizational Citizenship Behavior (OCB), and the Work Ethic of employees to improve their performance. This is certainly an urgency for companies to implement effective strategies to strengthen employee engagement as a key factor in creating a competitive advantage. This study aims to analyze the influence of Organizational Culture, Organizational Citizenship Behavior (OCB), and Work Ethic on Employee Performance. This approach uses a quantitative approach with a sewing division employee population of 892 employees. Sampling was carried out using purposive sampling, so that a total of 276 employees were obtained. The results of the analysis show that Organizational Culture, Organizational Citizenship Behavior (OCB), and Work Ethic have a significant influence on Employee Performance. This means that a good Organizational Culture provides clarity in instructing its tasks, even though collaboration between divisions still needs to be improved. A high OCB reflects the positive behavior of employees in helping others and contributing to an organization. In addition, a strong work ethic is able to support employees to work hard and be committed to the company.